SISTEM INFORMASI GEOGRAFIS PEMETAAN KAWASAN RAWAN KEBAKARAN MENGGUNAKAN METODE SEQUENTIAL PATTERN MINING - Revi Melia; Nurul Mutiah; Syahru Rahmayuda (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2023)
Land and forest fires occur every year in Indonesia, where the cause is human negligence or intentional related to forest deforestation. Land and forest fires, of course, can cause economic, health, social and cultural, ecological and environmental damage. One indicator that is useful as a determinant of the occurrence of land fires is hot spots. To manage hotspot data, data mining can be done, namely by using the sequential pattern mining method to obtain hotspot sequence patterns that will be used as indicators of land fires. In overcoming these problems, a Geographic Information System (GIS) was designed to map the areas prone to land fires in Kubu Raya Regency. The results of this study are maps of the distribution of land fire-prone areas and the pattern of occurrence of hotspots calculated using the sequential pattern mining method which is expected to assist relevant agencies in carrying out mitigation and prevention efforts for land fires, so as to produce the right decisions for handling land fires in the District. Kingdom Fortress. Based on the results of functionality testing using the black box testing method, the SIGPKRK application (Geographical Information System for Mapping Fire Prone Areas) that was built can run and is in accordance with the functions that have been designed. As for the results of testing the system interface using a questionnaire through the Google form which was filled in by 30 respondents, the SIGPKRK application obtained a percentage result of 85.9% which was included in the